Targeting Mitochondrial Biogenesis and Mitochondrial Substrate Utilization to Treat Obesity and Insulin Resistance, Respectively - Two Data-Driven Hypotheses - Hey-Mogensen, Martin; Clausen, Trine R (Current diabetes reviews, 2017)
The mitochondrion plays a critical role in cellular energy metabolism. For this reason it is considered as a plausible target for the treatment of metabolic diseases such as obesity and type-2 diabetes. Although several mitochondrial molecular targets have been suggested and investigated, currently there are no marketed drugs that target the mitochondrion to treat metabolic diseases. Through an investigation of current drugs and investigational compounds, two hypotheses have emerged: 1) inhibition of mitochondrial substrate utilization is associated with increased insulinstimulated glucose uptake; 2) stimulation of mitochondrial biogenesis is related to increased energy expenditure and potentially weight loss. The mode-of-action of both mechanistic hypotheses is currently unknown and potentially controversial since they contradict other experimental findings. However, the fact that both processes are stimulated by different types of compounds with different sites of action supports their potential existence. This review summarizes the data that support these two hypotheses; with the hope that this will stimulate further research and intensify the development of future drugs for the treatment of obesity and type-2 diabetes.